Association of Hospital Characteristics With Early SEP-1 Performance. (March 2020) - Liao, Jeff; Aaronson, Emily; Kim, Jungyeon; Liu, Xiu; Snydeman, Colleen; Goldfarb, Ilona; Black, Lauren; Filbin, Michael; Phillips, Michael T.; Mort, Elizabeth; Lee, Jarone
A variety of hospital characteristics, including teaching status, ownership, location, and size, have been shown to be associated with quality measure performance. The association of hospital characteristics, including teaching intensity, with performance on the Centers for Medicare & Medicaid Services (CMS) SEP-1 sepsis measure has not been well studied. Utilizing a statewide, all-payer database and the CMS Hospital Compare database, this study investigated the association of various hospital characteristics with early SEP-1 performance in 48 acute hospitals in Massachusetts. Hospital teaching intensity and Magnet designation did not have a statistically significant association with SEP-1 performance in multivariable linear modeling. However, SEP-1 performance was higher in smaller, for-profit hospitals with higher case mix index. This finding suggests that emergency department activity, hospital ownership, and patient complexity should be studied further across a larger geographic spectrum and longitudinally as hospitals implement efforts to reduce morbidity associated with sepsis.